The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00428-013-1428-y
|View full text |Cite
|
Sign up to set email alerts
|

In aggressive variants of non-Hodgkin lymphomas, Ezh2 is strongly expressed and polycomb repressive complex PRC1.4 dominates over PRC1.2

Abstract: Polycomb group (PcG) proteins are important for the regulation of hematopoiesis by regulating chromatin compaction and silencing genes related to differentiation and cell cycle. Overexpression of enhancer of zeste homologue 2 (Ezh2) and Bmi-1/PCGF4 has been implicated in solid organ cancers, while Mel-18/PCGF2 has been reported as a tumor suppressor. Detailed expression profiles of PcG proteins and their diagnostic significance in malignant lymphomas are still unknown. In this study, we analyzed the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 36 publications
0
29
1
Order By: Relevance
“…Overexpression of BMI-1 has been previously reported in gastric, ovarian, breast, head and neck, pancreatic and lung cancer, as well as in primary hepatocellular carcinoma (HCC) and endometrial carcinoma (8)(9)(10)(11)(12)(13)(14)(15)(16). In addition, BMI-1 overexpression has been identified in patients suffering from myelodysplastic syndrome, chronic myeloid leukemia, acute myeloid leukemia and lymphoma (17)(18)(19)(20). Previous studies have indicated that the increased BMI-1 expression was associated with tumor proliferation, invasion/metastasis, chemosensitivity and patient survival (Table I).…”
Section: Bmi-1 and Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…Overexpression of BMI-1 has been previously reported in gastric, ovarian, breast, head and neck, pancreatic and lung cancer, as well as in primary hepatocellular carcinoma (HCC) and endometrial carcinoma (8)(9)(10)(11)(12)(13)(14)(15)(16). In addition, BMI-1 overexpression has been identified in patients suffering from myelodysplastic syndrome, chronic myeloid leukemia, acute myeloid leukemia and lymphoma (17)(18)(19)(20). Previous studies have indicated that the increased BMI-1 expression was associated with tumor proliferation, invasion/metastasis, chemosensitivity and patient survival (Table I).…”
Section: Bmi-1 and Cancermentioning
confidence: 98%
“…Certain in vitro studies revealed that overexpression of BMI-1 can promote chemoresistance (23), whereas depletion of BMI-1 is able to enhance the chemosensitivity of HCC (15,37) and ovarian cancer cells (38,39). In a clinical setting, the overexpression of BMI-1 may facilitate drug resistance in hematological malignancies, including the myelodysplastic syndrome, chronic myeloid leukemia, acute myeloid leukemia and lymphoma (17)(18)(19)(20)40). In addition, BMI-1 has been demonstrated to play an important role in chemoresistance and radiosensitivity in breast cancer (41,42).…”
Section: Bmi-1 and Cancermentioning
confidence: 99%
“…26 Expression of EZH2 strongly associates with B-cell malignancies, with its high levels correlated with the Ki67 labeling index, lymphoma aggressiveness, and unfavorable prognosis. 33,34 The highest percentage of EZH2 positivity was found in 100% of Burkitt lymphomas, 87.5% of grade-3 FLs, and 85.7% of DLBCLs. Multivariate survival analysis identified EZH2 as the strongest prognostic predictor of inferior outcomes of MCLs.…”
mentioning
confidence: 99%
“…31,32 In human B-cell lymphomas, BMI1 overexpression is common in almost all subtypes. 33 Expression of BMI1 alone or in combination with EZH2 characterizes aggressive B-cell lymphomas with unfavorable prognosis. 27,33,34 Recently, a novel t(10;14)(p12;q32) translocation was identified in chronic lymphocytic leukemia and MCLs leading to IgH-BMI1 rearrangement and BMI1 overexpression 35 ; IgH-BMI1 rearrangement was acquired during tumor high-grade transformation and correlated with chemoresistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation